Legal Review of the Implementation of the Self-Protection Clause in Notarial Deeds If There is a Person Who Denies - Pratiwi, Carika Dian; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The legal force of the notary's self-protection clause in the deed if there is a party who denies it. 2) The legal consequences for a notary who does not include a self-protection clause in the notarial deed. This type of research is normative legal research. The approach method in this study is the statute approach. The type of data in this study is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study documents). The analysis in this study is prescriptive. The results of the study concluded: 1) The legal force of the notary's self-protection clause in the deed is legally limited because it is not explicitly regulated in the Notary Law. However, the inclusion of this clause is still permitted as long as it does not conflict with the law, morality, and public order. This clause functions as additional evidence that the notary has carried out his duties carefully and professionally. Although it does not exempt the notary from legal responsibility in the event of a dispute, the existence of this clause can strengthen the notary's position in the process of proving that he is not responsible for the material truth of the contents of the deed. This is important in dealing with the potential criminalization of the notary profession which often occurs due to denials from the parties. 2) The legal consequences for a notary who does not include a self-protection clause in a notarial deed are that it is not a violation of positive law, but has the potential to cause adverse legal impacts for the notary. Without this clause, the notary's position becomes weaker when facing lawsuits or accusations, especially regarding false information in the deed. This makes it difficult for the notary to show that he only recorded the wishes of the parties, not guaranteeing the truth of the material. From the perspective of Philipus M. Hadjon's legal protection theory, the absence of this clause means weakening preventive and repressive legal protection for notaries. Therefore, the inclusion of a self-protection clause should be standard practice in the making of notarial deeds as a form of legal protection and an effort to maintain professionalism in carrying out duties.Keywords: Applicant; Notarial Deed; Self-Protection Clause.